2016
DOI: 10.1021/acsami.6b02998
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Boron Precursor on the Growth and Optoelectronic Properties of Electrodeposited Zinc Oxide Thin Film

Abstract: Highly transparent and conductive materials are required for many industrial applications. One of the interesting features of ZnO is the possibility to dope it using different elements, hence improving its conductivity. Results concerning the zinc oxide thin films electrodeposited in a zinc perchlorate medium containing a boron precursor are presented in this study. The addition of boron to the electrolyte leads to significant effects on the morphology and crystalline structure as well as an evolution of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The characterization of the electrical and optical properties of the electrodeposited films can be particularly challenging due to the presence of a conductive substrate required by the electrodeposition process, which may interact with the optoelectronic properties of ZnO and interfere during the electrical measurements. The doping levels of the films were extracted from the measurement of the infrared reflection spectra of the film using the Drude model (according to ref ). Reflectance spectra were measured with a Fourier-transformed infrared spectrometer (Bruker Vertex 70) and a MCT detector.…”
Section: Methodsmentioning
confidence: 99%
“…The characterization of the electrical and optical properties of the electrodeposited films can be particularly challenging due to the presence of a conductive substrate required by the electrodeposition process, which may interact with the optoelectronic properties of ZnO and interfere during the electrical measurements. The doping levels of the films were extracted from the measurement of the infrared reflection spectra of the film using the Drude model (according to ref ). Reflectance spectra were measured with a Fourier-transformed infrared spectrometer (Bruker Vertex 70) and a MCT detector.…”
Section: Methodsmentioning
confidence: 99%
“…To date, numerous literature has been reported on ZnO NRs doped with several dopants. Yet there are very few reports on hydrothermally grown B-doped ZnO NRs [20,[32][33][34]. Herein, we have reported the enhancement of charge separation caused along with the addition of boron into ZnO NRs.…”
Section: Introductionmentioning
confidence: 86%
“…Among them, the usage of B doping is less common than of other elements. For deposition of B doped ZnO, inexpensive and uncomplicated methods, such as spray pyrolysis [10,11], sol gel [12][13][14] and electrodeposition, [15][16][17][18] can be applied. Chronoamperometry, one of the electrodeposition techniques, is widely used for film deposition because it is simple and economical.…”
Section: Introductionmentioning
confidence: 99%
“…In the study published by Calnan et al [17], B doped ZnO films were prepared by using zinc nitrate and boric acid solutions (1 at.% to 20 at.% B ratios) and SEM images presented the existence of grains with hexagonal faces for low B contents and the clustering of these grains for 20 at.% B content. Tsin et al [18] revealed that an increase in boric acid concentration changed the size of the columns from 180 nm to 600 nm and PL emission peak of the films shifted to higher energy.…”
Section: Introductionmentioning
confidence: 99%